2005
DOI: 10.1348/026151005x26732
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between theory of mind and metaphor: Evidence from children with language impairment and autistic spectrum disorder

Abstract: Happé (1993) proposed that theory of mind (ToM) understanding was necessary for comprehension of metaphorical expressions. The current study investigated the role of both ToM and language ability in metaphor understanding. Ninety-four children aged 8-15 years with communication impairments were grouped according to language ability and autistic symptomatology in the first instance, and then according to ToM performance. Their performance on a metaphor task was compared to 34 typically developing age-matched pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
260
4
28

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(320 citation statements)
references
References 39 publications
(55 reference statements)
16
260
4
28
Order By: Relevance
“…These and other pragmatic impairments have been attributed to concurrent deficits in social cognition (Baron-Cohen, 2000;Surian, Baron-Cohen, & van der Lely, 1996) and/or weak central coherence (Happé, 1997). However, identifying potential sources of pragmatic deficit is impeded by the variable cognitive and language profiles that characterise ASD (Kjelgaard & Tager-Flusberg, 2001;Norbury 2005a), meaning that the source of error is far from clear (Bishop, 1989).…”
Section: Typical and Atypical Development Of Referencementioning
confidence: 99%
“…These and other pragmatic impairments have been attributed to concurrent deficits in social cognition (Baron-Cohen, 2000;Surian, Baron-Cohen, & van der Lely, 1996) and/or weak central coherence (Happé, 1997). However, identifying potential sources of pragmatic deficit is impeded by the variable cognitive and language profiles that characterise ASD (Kjelgaard & Tager-Flusberg, 2001;Norbury 2005a), meaning that the source of error is far from clear (Bishop, 1989).…”
Section: Typical and Atypical Development Of Referencementioning
confidence: 99%
“…Par exemple, le degré auquel les enfants avec ou sans TSA convoquent le contexte linguistique afin de résoudre des cas d'ambiguïté lexicale dépend de leur niveau verbal et non du diagnostic [20]. De même, la compréhension des méta-phores n'est pas spécifiquement déficitaire dans l'autisme, mais dépend des compétences sémantiques [21]. En fait, il est plausible qu'un lexique peu flexible et réduit -lui-même effet d'un déficit pragmatique précoce (voir plus haut) -puisse bloquer la modulation du sens lexical requise pour créer une interprétation métaphorique.…”
Section: Au-delà Du Sens Littéralunclassified
“…Many studies indicate that children with ASD may have difficulty understanding metaphors (Happé, 1993(Happé, , 1995Norbury, 2005;Rundlabd & Annaz, 2010;Melogno, D'Ardia, Pinto, & Levi, 2012). The first experimental studies were conducted in the early 1990s, in the pioneering research of Happé (Happé, 1993(Happé, , 1995.…”
Section: Metaphor and Metonymy Understanding In Children With Asdmentioning
confidence: 99%
“…For example, Norbury (2005) showed that theory of mind is a necessary condition for metaphor comprehension but not the only one, because metaphor comprehension draws upon specific lexical notions and extralinguistic knowledge. In the aforementioned example "John is a rock", the feature "hardness" that is implicit in the term "rock" may be intended on a concrete, sensorial plane or on a psychological plane that calls for more abstractive cognitive processes.…”
Section: Metaphor and Metonymy Understanding In Children With Asdmentioning
confidence: 99%